2022
DOI: 10.3390/foods11040506
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols Prevent and Intervene in COVID-19 through Intestinal Microbiota

Abstract: Although all countries have taken corresponding measures, the coronavirus disease 2019 (COVID-19) is still ravaging the world. To consolidate the existing anti-epidemic results and further strengthen the prevention and control measures against the new coronavirus, we are now actively pioneering a novel research idea of regulating the intestinal microbiota through tea polyphenols for reference. Although studies have long revealed the regulatory effect of tea polyphenols on the intestinal microbiota to various g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Recent modeling studies have shown that various tea components are highly effective in blocking SARS-CoV-2 infection ( 24 , 25 , 47 , 48 ). In addition, tea polyphenols might suppress the virus through their beneficial effects on intestinal microbiota ( 49 ). It has yet to be determined whether habitual tea consumption may exert an effect against COVID-19 in exposed populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent modeling studies have shown that various tea components are highly effective in blocking SARS-CoV-2 infection ( 24 , 25 , 47 , 48 ). In addition, tea polyphenols might suppress the virus through their beneficial effects on intestinal microbiota ( 49 ). It has yet to be determined whether habitual tea consumption may exert an effect against COVID-19 in exposed populations.…”
Section: Discussionmentioning
confidence: 99%
“…The major bacterial phyla in the intestinal microorganisms comprise actinobacteria, Proteobacteria, Verrucomicrobia, and Fusobacteria [13]. Fundamental processes such as digestion, metabolism, and vitamin production in animal bodies are heavily reliant on the presence and activity of the gut microbiota [14].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Conversely, a wealth of species is often associated with a "healthy gut" [15]. The gut microbiota has the capability to generate enzymes facilitating the breakdown of polysaccharides and plant polyphenols, as well as the synthesis of certain vitamins, thereby contributing to the intestinal well-being of the host [14]. A state of harmonious equilibrium among bacteria is maintained within a healthy gastrointestinal system, where genetic and environmental factors play a role in determining the type, quantity, and proportion of gut microbiota.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…EGCG has entered phase 2/3 clinical trials. According to the strength of oxidation, the order of oxidation of EGCG and its three derivatives ((Epigalloeatechin)EGC, (Epieatechin gallate) ECG, (Epieatechin) EC) is: EGCG > EGC > ECG > EC [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Therefore, it can be speculated that the 3′,4′,5′-trihydroxyl group of the B ring in the EGCG structure is important for its antioxidant capacity.…”
Section: Research Progress Of Nrf2 In Inflammation-related Diseasesmentioning
confidence: 99%